Evaluasi Kinerja Kepala Sekolah dalam Pengembangan Kuriulum pada Sekolah UPT SMP Negeri 35 Medan - Neliwati; Azzahra Lubis, Fatimah; Fadilah, Aisyah; Kholis, Zidan (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine how the evaluation of the principal's performance in curriculum development at the UPT SMP Negeri 35 Medan school. In this research, the method used is descriptive qualitative research method and the data obtained is from the results of interviews, observations and documentation at UPT SMP Negeri 35 Medan school. In curriculum development, school principals need to cooperate with other parties in evaluating curriculum development. Because the principal will not be able to carry out all his duties well by himself. Need good cooperation with other teachers and the government in handling funds in order to form a good and correct curriculum development. Which is where the curriculum is a very important and decisive component in organizing education. As well as the curriculum also functions as a tool for achieving educational goals, if educational goals change then automatically the curriculum must also be changed.